GIS4EU, l'interoperabilità dei dati nell'UE - Mauro Salvemini; Laura Berardi; Valeria Mercadante; Francesco Buscemi (GEOmedia, 2010)
GIS4EU In Europe, spatial information is characterised by lack of harmonisation between datasets at different geographical scales, fragmented datasets and sources, gaps in availability and duplication of information. In this context the GIS4EU project aim is to create a common knowledge base and make spatial information more accessible according to standards and requirements of the INSPIRE Directive. Therefore, the project intends to develop a common data model in order to enable access to consistent and homogenous reference data provided by cartographic authorities of different countries and levels.